VARIAN GELOMBANG EEG NORMAL SEBAGAI FAKTOR PENYEBAB KESALAHAN DIAGNOSIS EPILEPSI - Suryani Gunadharma* (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION ELECTROENCEPHALOGRAPHY EEG IS THE MOST USEFUL TEST FOR ASSESSMENT OF EPILEPTIC PATIENTS HOWEVER EEG IS OFTEN OVERANALYZED ESPECIALLY BY INEXPERIENCED READERS EEG OVERINTERPRETATION IS COMMON AND PLAYS AS AN IMPORTANT CONTRIBUTOR OF MISDIAGNOSIS OF EPILEPSY IMPACTING SIGNIFICANTLY IN PATIENTS LIVES INTERICTAL EPILEPTIFORM DISCHARGES IED HAVE A STRONG CORRELATION WITH EPILEPSY NOT ALL SPIKE OR SHARPWAVES HAVE A RELATION WITH EPILEPSY